AMPLIFIKASI PROFESI GURU DALAM PROSES PENDIDIKAN TRANSFORMATIF PERSPEKTIF AL-GHAZALI - Akmal Mundiri; Afidatul Bariroh (Universitas Islam Negeri Ar-Raniry, 2018)
The era of globalization provides a great change to the world order as a whole. The change is faced together as a natural change because under no circumstances will change occur. Free market globalization at the local, regional and international levels will create uncertain changes. To face globalization needs to be realized in quality Indonesian society. Transformative education has a vision of transforming traditional society into modern society. As nowadays the Indonesian society is an agrarian society with ethics, aesthetics and agrarian personality not yet fully familiar with science and technology along with its development. The task of education is to change the civilization of society, especially in instilling and developing science and technology as well as ethics, aesthetics, and changes into the social system of society. One of the efforts in improving the quality of education is to improve the quality of teachers as the spearhead that interact directly with learners. In the scope of transformative education, teachers tend to rely on specialized specialist labor skills that will survive and compete in the coming century. Teachers at this time are expected to be figures who are able to manage the learning program by formulating instructional goals using appropriate methods and in accordance with the needs of learners. Teachers should have a personality competence that is charismatic and authoritative, wise in facing learners and able to be a good example in terms of attitude and spoken words.